Susunan Pancasila Yang Bersifat Hirarkis dan Berbentuk Piramidal, Sebagai Sistem Filsafat,dan Urgensi Pancasila Sebagai Sistem Filsafat - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Nanda Widyadinata; Sahara Yuliana; Yunandia Yunandia (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Pancasila, as the basis of the Indonesian state, is a philosophical system that underlies national and state life with the principles of divinity, humanity, unity, democracy and social justice. The background to this research focuses on the urgency of Pancasila in globalization and also rapid social change, where new challenges require adaptation so that Pancasila remains relevant and effective. The aim of the research is to analyze the hierarchical and pyramidal structure of Pancasila, the formulation of the relationship between the precepts which complement and qualify each other, as well as the dynamics and challenges faced by Pancasila as a philosophical system. The research method uses library research to collect and analyze data from various relevant sources. The research results show that Pancasila, with its hierarchical structure that positions the precepts in a mutually supportive order, functions as a strong moral and ideological guide. The relationship between the Pancasila principles complement each other and also clarify each other's principles, forming a coherent and comprehensive system. However, challenges such as globalization, social inequality and political dynamics require adjustment and adaptation to maintain the relevance of Pancasila. This research emphasizes the importance of further study and development to ensure that Pancasila remains the basis of a strong and effective state in the modern era.